The Prevalence of Generalized Anxiety Disorder Among Health Care Workers During the COVID-19 Pandemic: A Systematic Review and Meta-Analysis - Adibi, Amir; Golitaleb, Mohamad; Farrahi-Ashtiani, Iman; Pirani, Davoud; Yousefi, Kosar; Jamshidbeigi, Yousef; Sahebi, Ali (Frontiers in Psychiatry, 2021)
Introduction: Health care workers, due to be involved in caring for COVID-19 patients may experience various psychological problems including anxiety disorders. This study aimed to investigate the prevalence of Generalized Anxiety Disorder (GAD) among health care workers during the COVID-19 pandemic by systematic review and meta-analysis. Methods: The PRISMA guideline was used for conducting this study. Related keywords were searched in credited resources including ISC, Magiran, PubMed, Scopus, Web of Science, Cochrane, ProQuest, Science Direct, Google Scholar, and Embase to find the articles published on the prevalence of GAD among health care workers during the COVID-19 pandemic from the first of January to the end of June 2020. Meta-analysis was conducted by the random effects model. Results: In this study, 553 articles were initially identified, from which 19 studies were finally included in the meta-analysis. The results showed that the prevalence of GAD in health care workers based on the GAD-7 and GAD-2 instruments were 32.04% (95% CI: 26.89–37.19, I2 = 98.2%, p < 0.001) and 22.62% (95% CI: 9.01–36.24, I2 = 97.7%, p < 0.001). The overall prevalence of GAD was obtained 30.5% (95% CI: 25.58–35.42, I2 = 98.4%, p < 0.001). Conclusion: This study showed a relatively high GAD prevalence, as one of the fundamental psychological problems, among health care workers during the COVID-19 pandemic. Therefore, health system managers should implement preventive strategies to protect health staff from contracting the virus and monitor them for psychological problems and provide them with supportive measures if necessary.